Effect of alloyed Lu, Hf and Cr on the oxidation and spallation behavior of NiAl. (September 2017) - Zhao, Chunshan; Zhou, Yuhua; Zou, Zhonghua; Luo, Lirong; Zhao, Xiaofeng; Guo, Fangwei; Xiao, Ping
Highlights: Lu was more effective than Hf in inhibiting the θ-α-Al2 O3 transformation. The presence of Lu significantly contributed to the oxygen transport rate. S and C segregated not only at the alloy/scale interface, but also within the scale. Both Lu and Hf could significantly improve the spallation resistance. The beneficial effect of Lu in NiAl can be easily overcompensated by Cr. Abstract: The influences of alloyed Lu, Hf and Cr on the oxidation and spallation behavior of NiAl were investigated. Although Lu has a "block effect" of Al as Hf does, the oxidation rate of Lu-doped NiAl is significantly higher, due to: (1) inhibitation of θ- to α-Al2 O3 transformation in early oxidation stage; (2) stronger scale grain refinement effect and enhanced oxygen transport rate. Segregation of S and C occurs not only at the alloy/scale interface, but also within the scale. Both Lu and Hf can significantly improve the scale adherence. However, This beneficial effect can be easily overcompensated by Cr.